Factors Affecting the Performance of Tax Authorities with Tax Compliance as a Moderating Variable: An Empirical Study on Small and Medium Enterprises in West Jakarta - Waluyo Waluyo (Jurnal Ilmiah Akuntansi, 2024)
Achieving tax revenue targets is a significant concern for the government. A lack of taxpayer knowledge about their tax obligations, coupled with frequently changing and complex tax regulations, leads to taxpayer negligence and non-compliance, ultimately impacting tax revenues. This quantitative research examines the factors affecting the performance of tax authorities, with a focus on tax compliance as a moderating variable, specifically among small and medium enterprises (SMEs) in West Jakarta. Data were collected using a questionnaire distributed to 100 SME actors in the area. The study's results indicate that tax knowledge does not significantly impact the performance of tax authorities. In contrast, tax complexity and tax compliance do significantly influence tax authority performance. Additionally, tax compliance does not strengthen the relationship between tax knowledge and tax complexity on the performance of tax authorities. These findings suggest that to improve tax authority performance and increase tax revenues, efforts should focus on simplifying tax regulations and enhancing tax compliance rather than solely increasing tax knowledge among taxpayers. This research provides valuable insights for policymakers and tax administrators aiming to optimize tax authority performance and compliance among SMEs.